Protective Effects of Glucagon-Like Peptide-1 Analog on Renal Tubular Injury in Mice on High-Fat Diet - Guo, Honglei; Li, Hongmei; Wang, Bin; Ding, Wei; Ling, Lilu; Yang, Min; Gu, Yong; Niu, Jianying (Cellular physiology and biochemistry, 2017)
Aims: The study aimed to investigate the renoprotective effect of glucagon-like peptide-1 (GLP-1) against renal tubular injury in C57BL/6 mice induced by a high-fat diet (HFD). Methods: Twenty C57BL/6 mice were fed HFD for 12 weeks. Ten of these mice were treated with GLP-1 at 200 µg/kg subcutaneously twice daily for 4 weeks (HFDG group), and the other ten mice received vehicle only (HFD group). Ten mice fed standard rodent chow served as controls (Con group). Body weight, kidney weight, food intake, and systolic blood pressure were measured. The expression of endoplasmic reticulum stress (ERS) markers (BIP, p-eIF2α, ATF4, and CHOP) and apoptosis in the kidney were examined utilizing western blotting, immunohistochemistry and TUNEL, respectively. Angiotensin II and angiotensin II type 1 receptor (AT1R) were examined by ELISA. Human proximal tubule epithelial cells (HK2) were treated with GLP-1(150 nM) followed by treatment with palmitic acid (500 nM [PA]) for 24 h. HK2 cells treated with BSA were used as controls. The protein levels of ERS markers, apoptosis-associated protein, and AT1R were measured by western blotting. Results: Increase of body weight, food intake, and systolic blood pressure was less pronounced in GLP-1 treated HFDG mice compared to HFD mice. The levels of ERS markers (BIP, p-eIF2α, ATF4, and CHOP) and apoptosis decreased following GLP-1 treatment in vivo and in vitro (p<0.05). Increased AT1R induced by HFD and PA were blocked with GLP-1 treatment. In contrast, the level of angiotensin II after GLP-1 treatment was not significantly different between the HFD and HFDG mice. Conclusion: The study indicated that saturated fatty acids induced ERS and apoptosis in the kidney and increased AT1R expression. GLP-1 treatment exerted renoprotective effects against saturated fatty acid-induced kidney tubular cell ERS and apoptosis together with inhibition of AT1R expression in vivo and in vitro.